2008
DOI: 10.1128/jvi.01319-07
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma-Associated Herpesvirus ori - Lyt -Dependent DNA Replication: Involvement of Host Cellular Factors

Abstract: Herpesvirus lytic DNA replication requires both the cis-acting element, the origin, and trans-acting factors, including virally encoded origin-binding protein, DNA replication enzymes, and auxiliary factors. Two lytic DNA replication origins (ori-Lyt) of Kaposi's sarcoma-associated herpesvirus (KSHV) have been identified, and two virally encoded proteins, namely, RTA and K8, have been shown to bind to the origins. In this study, we sought to identify cellular factors that associate with ori-Lyt by using DNA af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
111
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(117 citation statements)
references
References 45 publications
6
111
0
Order By: Relevance
“…These results are in agreement with previous studies suggesting that HSV-1 replication may be dependent upon HR events requiring both viral and cellular proteins (86). Indeed, MSH proteins have been identified in the replication compartments of various herpesviruses (13,69,75). Factors such as MRN and MSH are both involved in the control of HR and most likely present in AAV RCs because they are recruited by HSV-1-encoded factors for its own replication.…”
supporting
confidence: 93%
“…These results are in agreement with previous studies suggesting that HSV-1 replication may be dependent upon HR events requiring both viral and cellular proteins (86). Indeed, MSH proteins have been identified in the replication compartments of various herpesviruses (13,69,75). Factors such as MRN and MSH are both involved in the control of HR and most likely present in AAV RCs because they are recruited by HSV-1-encoded factors for its own replication.…”
supporting
confidence: 93%
“…For example, several cellular genes have been shown to mediate KSHV entry in different types of cells (1,31,46). Other cellular genes, such as those for topoisomerase I, topoisomerase II, and poly(ADP-ribose) polymerase 1 (PARP-1), were shown to function during KSHV lytic DNA replication (58).…”
mentioning
confidence: 99%
“…Earlier studies have shown the binding of DNA-PK and Ku70-Ku80 to the replication origins of herpes simplex virus type 1 (HSV-1) and Kaposi's sarcoma-associated herpesvirus (KSHV) (Taylor & Knipe, 2004;Wang et al, 2008), indicating that Ku70-Ku80 is critically involved in the replication of these two viruses. This study finds that Ku80 binds to the three ZRE in the BHLF1 promoter, which overlaps with oriLyt.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Zta is known to recruit basal transcription factors, including TFIID and TFIIA, to promoters by binding to ZRE (Lieberman & Berk, 1994). Accordingly, Zta and Ku80 may cooperate with each other to activate the transcription of EBV lytic genes.Earlier studies have shown the binding of DNA-PK and Ku70-Ku80 to the replication origins of herpes simplex virus type 1 (HSV-1) and Kaposi's sarcoma-associated herpesvirus (KSHV) (Taylor & Knipe, 2004;Wang et al, 2008), indicating that Ku70-Ku80 is critically involved in the replication of these two viruses. This study finds that Ku80 binds to the three ZRE in the BHLF1 promoter, which overlaps with oriLyt.…”
mentioning
confidence: 99%